Pengaruh Student Engagement terhadap Communication Skill Mahasiswa - Kismiani Kismiani; Hesti Sadtyadi; Ratna Setyaningsih (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Having good communication skills can make someone easily accepted in an organization and will get a positive response in the communication that has been built. The purpose of this study was to see if there is a significant influence between Student Engagement and Student Communication Skills. The research method used is a quantitative research method. Data were collected through a google form using a Likert scale of 1-5 from 62 respondents from the Dharmaduta Department Student Association of the Raden Wijaya State Buddhist College which will later be tested for validity, reliability, and hypothesis influence. The results of the study using a simple linear regression test showed a significant value (Sig.) for student engagement (X) of 0.000 and R Square of 0.409, a significant value <0.05 so that H0 was rejected and Ha was accepted, meaning that student engagement has a significant effect on communication skills. Based on these results, it can be concluded that student engagement has a role in shaping student communication skills by 40.9%.